Prevalence and Predictors of Posttraumatic Stress and Depression Symptoms Among Syrian Refugees in a Refugee Camp. Issue 1 (January 2018) - Acarturk, Ceren; Cetinkaya, Mustafa; Senay, Ibrahim; Gulen, Birgul; Aker, Tamer; Hinton, Devon
Abstract : Abstract: Turkey is hosting the majority of Syrian refugees. The current study investigates the prevalence of probable posttraumatic stress disorder (PTSD) and depression among adult Syrians residing in a camp ( N = 781) and potential predictors. The Impact of Event Scale–Revised was used to measure PTSD and the Beck Depression Inventory depression. Probable PTSD prevalence was 83.4%, with predictors being female sex (odds ratio [OR], 4.1), previous mental health problems (OR, 4.5), life threat (OR, 3.0), and injury of a loved one (OR, 1.8). Probable depression prevalence was 37.4%, with predictors being female sex (OR, 5.1), previous mental health problems (OR, 2.9), having a loved one who was tortured (OR, 1.7), and not being satisfied at the camp (OR, 1.7). The current study reveals high rates of probable PTSD and depression among Syrian refugees and highlights vulnerabilities such as great risk for women of having psychopathology.